Проблеми і потенційні можливості забезпечення інформаційної безпеки бізнесу в умовах воєнного стан - Озарко, К.С.; Опотяк, Ю.В.; Андрухів, Т.В. (Вісник економічної науки України, 2025)
Стаття присвячена проблемам, потенційним можливостям забезпечення інформаційної безпеки бізнесу в умовах воєнного стану. Проаналізовано тенденції кількості кіберзлочинів в Україні за період 2016-2024 рр. Аналіз складних сучасних умов господарювання сприяв виявленню основних проблем забезпечення інформаційної безпеки вітчизняного бізнесу. Систематизовано потенційні можливості, напрямки зміцнення і розвитку інформаційної безпеки вітчизняних організацій. The article is devoted to the problems and potential opportunities of ensuring business information security under martial law. A reliable protection system becomes the basis for the continuity and systematic nature of business processes, preservation of reputation, protection of commercial and personal information, etc. In times of war, the role of the information environment in risk management, strategic management decision-making, interaction with government agencies, partners (including international ones), customers, etc. increases significantly. Accordingly, the lack of an adequate level of information security can lead to serious financial, legal, image and other losses. The study of business information security under martial law is extremely relevant and has practical implications for monitoring, analyzing, assessing risk and developing effective approaches to preventing and countering threats in the digital environment. The article analyzes the trends in the number of cybercrimes in Ukraine for the period 2016-2024. The analysis of complex and complex modern business conditions has helped to identify the main problems of ensuring information security of domestic business. The article describes the trends in the development of the Ukrainian cybersecurity market and the cloud security market in Ukraine. The article systematizes the potential opportunities and directions for strengthening and developing information security of domestic organizations. Information security of domestic business under martial law is not only a purely technical problem. Today, it has become a strategic component of national stability and security. Despite serious challenges, domestic businesses have access to new opportunities. This includes government support, international assistance, and technological innovations. Implementation of targeted actions in the area of development and strengthening of information security will allow domestic business not only to avoid losses but also to become the basis for its stable development in the post-war period.